TERMINOLOGY OF TEACHING METHODS IN LEARNING LANGUAGE - Khoshimova N.A,; Galiakberova Albina , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
To begin with, the high status of English in a situation of globalization of society means that it is widely used in international purposes and there is a need for graduates with a sufficient level of language training. Moreover, the first step in the motivation of students to study English is an understanding that English language is necessary for both personal and national development, as well as for international contacts in all areas of human activity. Professional communication, processes of cognition, thinking and communication are key concepts of modern reality.